Stress Analysis of PCI-Girder Precast Concrete Segmental Bridge Based on SNI 1725:2016 (Case Study: Konaweha River Bridges, Southeast Sulawesi) - Puspitasari, Nia Dwi; Kartini, Wahyu; Alfiansyah, Achmad Dzulfiqar (Journal of Civil Engineering, Planning and Design, 2023)
A prestressed bridge is an alternative way of structural design because of the ease of procurement and installation. For long-span bridges, prestressed beams only require minimum cross-sectional dimensions along with reliable performance. A prestressed concrete beam is always made in several segments to facilitate delivery. It is necessary to analyse and control the stress that occurs due to the external load and the loss of prestress. This study aims to provide a detailed stress analysis of PCI-girder precast concrete segmental bridges, considering the provisions and guidelines specified in SNI 1725:2016. Four stages of construction will be controlled. Namely at the transfer stage, the after-loss of the prestressed stage, the composite beam stage, and the service stage. The tensile and compressive stress analyses will be carried out on the upper side of the bridge surface, the upper side of the girder, and the bottom. If tensile stress occurs, it indicates that the girder is not capable of withstanding the applied load, and additional anchorages need to be installed at each joint between segments. The result obtained from the stress analysis conducted in this study is that no tensile stress is found in any critical sections of the girder. The stress that occurs has fulfilled the design capacity, without any tensile stress occurring in the bridge.